Determining the cause-and-effect relationships responsible for coal properties. 3. Association of chemical elements and role of indicators and accompanying elements in assessing the variability of beds’ mineral composition; Coke and Chemistry; Vol. 60, iss. 3 - Ivanov V. P. Vladimir Petrovich (2017, 2017)
Title screen